Case report: Genetic analysis of a novel intronic inversion variant in the SPTB gene associated with hereditary spherocytosis - Xi, Bixin; Liu, Siying; Zhu, Yongbing; Zhang, Dedong; Zhang, Yu; Liu, Aiguo (Frontiers in Genetics, 2023)
Background: Hereditary spherocytosis (HS) is a congenital haemolytic anaemia attributed to dysregulation or abnormal quantities of erythrocyte membrane proteins. Currently, the most common erythrocytic gene, spectrin β (SPTB), variants are located in exons and give rise to mRNA defects. However, the genetic characteristics and pathogenic mechanisms of SPTB intronic variants are not completely understood. This study aimed to analyse a rare intronic inversion variant in the SPTB gene associated with HS, and explore the impact of the variant on SPTB mRNA splicing.The clinical manifestations of the patient were summarised and analysed for spherocytosis phenotype diagnosis. The pathogenic variant was identified in the proband using targeted nextgeneration and Sanger sequencing. RNA sequencing was performed to analyse whether SPTB gene splicing and expression were affected.Results: Targeted next-generation sequencing identified a novel disease-associated intronic inversion variant of the SPTB gene in the proband. The inversion variant was located between intron 19 and 20, and contained the entire exon 20 and partial sequences of adjacent introns. Sanger sequencing confirmed that the intronic inversion variant only appeared in the genome of the proband, not in his parents. RNA sequencing revealed that the variant could result in the skipping of exon 20 and reduced expression of SPTB mRNA.This study identifies a rare intronic inversion variant in the SPTB gene associated with hereditary spherocytosis. The pathogenic variant can lead to exon 20 skipping and decreased SPTB gene expression. This finding has not been previously reported in any literature. This study can expand the intronic variant spectrum of the SPTB gene, deepen our understanding of HS pathogenesis, and contribute to the genetic diagnosis and clinical management of patients.